Steric and energetic studies on adsorption of toxic arsenic ions by hematite nano-rods from laterite highlighting the impact of modification periods - Dina Mostafa; Nabila Shehata; Mashael D. Alqahtani; May N. Bin Jumah; Nahaa M. Alotaibi; Noof A. Alenazi; Hassan A. Rudayni; Ahmed A. Allam; Wail Al Zoubi; Mostafa R. Abukhadra (Scientific Reports)
Abstract This study presents a facile, cost-effective hydrothermal transformation of natural lateritic iron ore into hematite nanorods, offering significant economic and technical benefits for the remediation of toxic arsenic ions. Lateritic iron ore was subjected to alkaline modification for different durations (12 h (HM12), 24 h (HM24), 36 h (HM36), and 48 h (HM48)), leading to morphological evolution into nanorod structures (2D) with variations in surface area, crystallinity, and adsorption efficacy for arsenate (As(V)) ions. Comprehensive characterization confirmed significant structural and physicochemical modifications. X-ray diffraction (XRD) analysis revealed a shift in peak positions and intensity reduction, indicative of lattice strain and increased surface defects. Fourier-transform infrared spectroscopy (FT-IR) confirmed modifications in the Fe–O coordination, and Brunauer–Emmett–Teller (BET) surface area analysis demonstrated a notable increase in surface area, with HM36 exhibiting the highest value (154.7 m2/g). Adsorption experiments indicated that HM36 achieved the highest As(V) removal capacity (151.4 mg/g), followed by HM48 (138.2 mg/g), HM24 (125.4 mg/g), and HM12 (113.8 mg/g). Advanced equilibrium modeling revealed steric and energetic parameters governing the adsorption mechanism, with HM36 exhibiting the highest density of active sites (Nm = 67.9 mg/g). Each active site accommodated up to three As(V) ions, emphasizing the significance of multi-ionic interactions and vertical stacking at the adsorption interface. The adsorption energy, evaluated using both classic models (< 4 kJ/mol) and advanced statistical physics models (< 9 kJ/mol), confirmed a predominantly physical and exothermic adsorption mechanism. Thermodynamic evaluations further supported the spontaneous and favorable nature of As(V) adsorption across all modified hematite derivatives. The ease of synthesis, low-cost natural precursor, improved adsorption efficiency, and recyclability highlight the potential application of these hematite nanorods in real-world wastewater remediation. The findings suggest that HM36 is a highly efficient and scalable adsorbent for arsenic removal, offering sustainable solutions for industrial and agricultural wastewater treatment.